2015
DOI: 10.1016/j.cplett.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure stability of 1,1-diamino-2,2-dinitroethene (FOX-7): H/D isotope effect

Abstract: H/D substitution was used to gain insight into the role of hydrogen bonding (HB) on the high-pressure stability of FOX-7. Raman measurements were performed on single crystals of deuterated FOX-7 (FOX-7-d 4) compressed to 40 GPa. Comparison of present and previously published results for FOX-7 revealed that deuteration: (i) does not affect chemical stability to 40 GPa, (ii) removes spectral changes observed at 2 GPa, (iii) does not affect the pressure onset for the 4.5 GPa phase transition, and (iv) lifts the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…1,1-Diamino-2,2-dinitroethene (DADNE or FOX-7) is one of the most promising insensitive HE crystals, with performance comparable to cyclotrimethylenetrinitramine (RDX). FOX-7 has a relatively simple molecular structure, and its molecular and crystalline characteristics are similar to those of other known IHE crystals, including triaminotrinitrobenzene (TATB). , Thus, FOX-7 is an attractive prototype IHE crystal. Since its synthesis in 1998, considerable experimental efforts have been made to understand its crystal structures at extreme pressures and temperatures. It was reported that the ambient structure of FOX-7, α phase (monoclinic, P 2 1 / n ), can transform to three HT (β, γ, and δ) and two HP (α′ and ε) phases. The crystal structures of HT, ambient pressure, phases β (>386 K, orthorhombic, P 2 1 2 1 2 1 ), and γ (>446 K, monoclinic, P 2 1 / n ) have been determined, but the δ phase (>483 K) structure remains unresolved …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,1-Diamino-2,2-dinitroethene (DADNE or FOX-7) is one of the most promising insensitive HE crystals, with performance comparable to cyclotrimethylenetrinitramine (RDX). FOX-7 has a relatively simple molecular structure, and its molecular and crystalline characteristics are similar to those of other known IHE crystals, including triaminotrinitrobenzene (TATB). , Thus, FOX-7 is an attractive prototype IHE crystal. Since its synthesis in 1998, considerable experimental efforts have been made to understand its crystal structures at extreme pressures and temperatures. It was reported that the ambient structure of FOX-7, α phase (monoclinic, P 2 1 / n ), can transform to three HT (β, γ, and δ) and two HP (α′ and ε) phases. The crystal structures of HT, ambient pressure, phases β (>386 K, orthorhombic, P 2 1 2 1 2 1 ), and γ (>446 K, monoclinic, P 2 1 / n ) have been determined, but the δ phase (>483 K) structure remains unresolved …”
Section: Introductionmentioning
confidence: 99%
“…The α′ phase was indicated to have the same space group as the α phase . However, the ε-phase crystal structure has not been determined, despite considerable experimental and computational efforts. , Significant changes in the optical spectra and X-ray , and neutron powder diffraction patterns have suggested a substantial structural transformation. It was speculated that the ε phase can be amorphous or partially decomposed or assume plane layers .…”
Section: Introductionmentioning
confidence: 99%
“…1,1-Diamino-2,2-dinitroethene (C 2 (NO 2 NH 2 ) 2 , FOX-7, or DADNE) is an extremely promising insensitive high-explosive (IHE) crystal with excellent performance, low sensitivity to initiation, and a relatively simple molecular structure. Because of these attractive characteristics, FOX-7 is viewed as a prototypical IHE crystal, and there have been considerable efforts to identify and understand its microscopic response at pressure and temperature conditions relevant to its initiation. In particular, detailed knowledge of the high-pressure response is essential for understanding its structural and chemical stability/insensitivity in terms of the relevant molecular and crystalline processes. Additionally, determination of the pressure dependence of the lattice parameters is required to develop accurate equation of state (EOS) models for describing the continuum response of FOX-7.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report on the phase diagram and decomposition of single crystals of 1,1-diamino-2,2-dinitroethene (FOX-7, C 2 (NO 2 ) 2 (NH 2 ) 2 ), an energetic material with excellent performance and low initiation sensitivity. Because of these attractive characteristics, FOX-7 is viewed as a prototypical insensitive high explosive (IHE) and considerable experimental efforts have been made in the past to understand its polymorphic behavior at high pressures and temperatures. …”
Section: Introductionmentioning
confidence: 99%